The semiotics of the ritual meal in the "Didache" - Wolmarans, Johannes L. P. (Acta patristica et byzantina, 2005)
The Didache communities originated against the background of social disintegration accompanying policies of urbanisation and commercialisation practised by the Roman authorities. As an alternative society, this radical religious reaction supplied in its communal meal food for the poor to survive. The meal is also connected with "soul food", or the wisdom necessary to cope with life. Confession of faults stimulates spiritual growth. On a social level, the meal signifies a moral boundary between insiders and outsiders, and establishes a global social support system. Ideologically, the meal imparts and strengthens a dualistic view of the world. God in heaven determines human history, and desires prayers of thanksgiving as sacrifices. A unified and perfect Christian community precedes the coming Rule of God. No explicit or implicit reference to the real presence of the body and the blood of the Christ is made. Jesus is viewed as the mediator of this new community and of the knowledge which underpins its morality and ethics. The Eucharistic practices of the Didache in this way reflect a pre-Christological phase of Christianity.